Determinan Perilaku Pasien dalam Pengobatan Tradisional dengan Media Lintah (Studi pada Pasien Terapi Lintah di Desa Rengel Kecamatan Rengel Kabupaten Tuban) The Determinant of Patient Behavior of Traditional Remedy with Leeches Media (The Study of Leech - Ella Mardiana Safitri; Novia Luthviatin; Mury Ririanty (Pustaka Kesehatan, 2016)
Health is very important for humans to survive and do activities, but everyone must have felt the pain. A sick person would seek treatment with a variety of ways to cure the disease. Health seeking behavior in society is very varied, one of them is by making use of traditional medicine. Traditional medicine remains desirable communities in Indonesia, though modern health care has grown. The number of people who use traditional medicine remains high. One of the traditional medicine that exists today is the traditional treatment using leeches media. Since the first until now, the use of medical leeches for the treatment interests people. Leech therapy has began being implemented in Indonesia at this moment. One of the leech therapy practice is located in District Rengel Tuban. This study aimed to analyze the determinants related to patient behavior in traditional medicine by media leeches on the location of the practice of leech therapy in the village of the District Rengel Rengel Tuban. This research was analytic research with a quantitative approach and using a cross sectional study design. These results showed that there was a significant correlation between knowledge, attitudes, important person as a reference, facilities, and services to the behavior of the traditional treatment with leeches media. Keywords: behaviour, tradiotional remedy, leech therapy